2022
DOI: 10.1126/sciadv.abn7097
|View full text |Cite
|
Sign up to set email alerts
|

A myocardial infarct border-zone-on-a-chip demonstrates distinct regulation of cardiac tissue function by an oxygen gradient

Abstract: After a myocardial infarction, the boundary between the injured, hypoxic tissue and the adjacent viable, normoxic tissue, known as the border zone, is characterized by an oxygen gradient. Yet, the impact of an oxygen gradient on cardiac tissue function is poorly understood, largely due to limitations of existing experimental models. Here, we engineered a microphysiological system to controllably expose engineered cardiac tissue to an oxygen gradient that mimics the border zone and measured the effects of the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 84 publications
1
8
0
Order By: Relevance
“…The constructed hypoxic microenvironment model is not accurate enough, thus affecting the experimental results. In vitro bone-on-a-chip platforms are expected to realize accurate reconstruction of the oxygen concentration and gradient observed in vivo [ 81 ].…”
Section: Construction Of Hypoxic Microenvironment Using Microfluidic ...mentioning
confidence: 99%
“…The constructed hypoxic microenvironment model is not accurate enough, thus affecting the experimental results. In vitro bone-on-a-chip platforms are expected to realize accurate reconstruction of the oxygen concentration and gradient observed in vivo [ 81 ].…”
Section: Construction Of Hypoxic Microenvironment Using Microfluidic ...mentioning
confidence: 99%
“…130 To investigate the effects of different oxygen concentration gradients on cardiomyocytes, Rexius-Hall and his colleagues designed a myocardial infarct border-zone-on-a-chip. 131 They demonstrated that different oxygen gradients had an impact on calcium wave conduction velocity, systolic stress, and gene expression in cardiac tissue. These alterations resembled the characteristics of arrhythmia onset.…”
Section: Investigating the Development Of Cardiovascular Disease Usin...mentioning
confidence: 99%
“…Reproduced under the terms of the Creative Commons Attribution‐NonCommercial license (CC BY‐NC). [ 126 ] Copyright 2022, The Authors, published by American Association for the Advancement of Science. c) The image of an assembled 15‐chamber HoC.…”
Section: Life Support System Inside Hoc Devicesmentioning
confidence: 99%
“…An easy yet effective approach to control oxygen concentration in cell culture chambers was reported by an oxygen permeable microfluidic device made out of PDMS (Figure 5b). [ 126 ] Cells were cultured under a 0–20% linear oxygen gradient via one channel continuously perfused with air and the other with nitrogen. Oxygen can also be consumed by pyrogallol, [ 127 ] dissolved ascorbate, [ 128 ] or Na 2 SO 3 [ 129 ] to recreate hypoxic (<10%) to anaerobic systems, or kept at atmospheric levels (21%), or increased to improve oxygenation of microtissues.…”
Section: Life Support System Inside Hoc Devicesmentioning
confidence: 99%
See 1 more Smart Citation